Human resource management practices in Oman: a systematic review and synthesis for future research - Nasser Al Harrasi; Badriya Al Balushi; Samira Al Khayari; Maryam Al Rashdi (Cogent Business & Management, 2024)
This study is a systematic review of literature related to human resource management (HRM) practices in the Sultanate of Oman. The study aimed to advance research and practice related to HRM practices in the context of Oman. The study evaluates the effectiveness of HRM practices in enhancing organisational performance and relationships with other variables. The study analyses and synthesis 117 relevant publications. The findings reveal that Out of the 117 relevant publications that were analysed, 85.4% comprised empirical studies, with the majority using quantitative research methods. The primary industry from where the data were collected was education, and Sultan Qaboos University contributed the highest percentage of studies. The study found that HRM practices such as compensation management, training and development, and localisation policy face significant challenges and, therefore, require further research. Moreover, demographic factors such as gender diversity should be considered when designing HRM practices. Effective HRM practices positively impact organisational performance, employee satisfaction, and retention. This study provide implications for theory, practices and future research in the field of HRM practices in Oman.
Keywords: 650; Human resource management; practices; systematic review; future research; Oman